Exploring the Impact of Fear of Missing Out on Perceived Ease of Use and Usage Decisions in Digital Platforms - Zoraifi, Renata; Agung, Ignatius Wiseto Prasetyo; Arifin, Samsul (JOURNAL OF ADVANCED STUDIES IN MANAGEMENT, 2024)
This research endeavors to examine the mediating function of perceived ease of use within the context of the relationship between Fear of Missing Out (FOMO) and usage decisions among Generation Z users of digital platforms. Employing a quantitative research design, a total of 125 participants were engaged through an online survey instrument. The collected data were subjected to analysis utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that FOMO exerts a significant impact on usage decisions, both directly and indirectly through perceived ease of use, underscoring the critical role of user perception in the adoption of technology. These findings enhance the comprehension of the psychological and technological determinants influencing decision-making and offer practical recommendations for platform developers aiming to engage Generation Z.